Enhanced QoS Performance with Throughput Aware Effective Communication in VANETs - Khodayer Al-Dulaimi, Aymen Mohammed; Alkhazraji, Nejood; Mlket Almutoki, Sabah Mohammed; Alkhayyat, Ahmed H. R.; Abbas, F.H. (International Conference on Engineering Technology and their Applications (Online), 2023)
Vehicular Ad-Hoc Network (VANET) is a highly trending and developing technology for the future world where in all the place highly intelligent communication is required. In VANETs the intelligently information is transmitted from one place to another with the base transmission model such as vehicle based and as well infrastructure-based communication. Unfortunately, wireless transmission standard uses IEEE802.11p and ground way communication model which can easily get affected by the external environment that results in the increase of packet loss and delay during communication. For that purpose, in this paper Enhanced QoS Performance with Throughput Aware Effective Communication (EQPTAE) is developed that mainly concerned with effective network model creation, collision detection and collision avoidance. Hence vehicle perform multi-hop communication in a highly frequent manner where a greater number of connection loss occur here with the help of effective congestion control communication becomes highly traffic free which leads to enhance the communication quality and throughput utility at each instant of time. In order to create this network in practical way the software called NS2 is used which is highly suitable for vehicular communication and as well the parameters which are used for the performance analysis are packet delivery ratio, end-to-end delay, routing overhead, and energy efficiency. To perform comparative analysis the earlier researches which are used in this article are ICFDB and the RSUCI. From the results it is understood that the proposed EQPTAE achieves maximum delivery ratio and efficiency and as well minimum delay and overhead when compared with the earlier methods.